2000
DOI: 10.1001/archfami.9.7.631
|View full text |Cite
|
Sign up to set email alerts
|

National Patterns of Physician Activities Related to Obesity Management

Abstract: Specific interventions to address obesity are infrequent in visits to US physicians. Obesity is underreported and interventions are only moderately likely among patients identified as obese, even for those with serious obesity-related comorbidities.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

17
149
2

Year Published

2003
2003
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 188 publications
(168 citation statements)
references
References 16 publications
17
149
2
Order By: Relevance
“…5,6 In the present report, we describe a successful weight-loss program in clinical practice focusing on assessment of cardiovascular risk factors (lipid disorders, blood pressure, diabetes, metabolic syndrome, and smoking) and lifestyle modification with diet and exercise. The program uses a dietitian at 2 visits.…”
Section: Discussionmentioning
confidence: 99%
“…5,6 In the present report, we describe a successful weight-loss program in clinical practice focusing on assessment of cardiovascular risk factors (lipid disorders, blood pressure, diabetes, metabolic syndrome, and smoking) and lifestyle modification with diet and exercise. The program uses a dietitian at 2 visits.…”
Section: Discussionmentioning
confidence: 99%
“…14 Yet, studies have documented the underuse of lifestyle modification counseling in ambulatory care settings. [15][16][17][18] There has been little exploration of whether counseling frequency varies by patient race, and there is conflicting evidence within this literature. For example, one study reported that African-Americans were more likely to receive lifestyle counseling, 15 while another study of obese persons reported statistical trends for whites to receive such counseling more often.…”
Section: Introductionmentioning
confidence: 99%
“…For example, one study reported that African-Americans were more likely to receive lifestyle counseling, 15 while another study of obese persons reported statistical trends for whites to receive such counseling more often. 18 We are unaware of prior research exploring similar variations in physician practice patterns among patients with diabetes.…”
Section: Introductionmentioning
confidence: 99%
“…4,5 However, less than half of obese patients (body mass index [BMI] ! 30) report receiving physician advice, 4,6,7 with those who are in poorer health, more obese, middle-aged, female, and more educated more likely to receive advice. 4,8,9 Physician counseling about weight loss may be particularly important in nonmetropolitan areas, where residents are more likely to be obese, to exercise less, and to have poorer diets compared with suburban residents.…”
mentioning
confidence: 99%